2006
DOI: 10.1097/01.fpc.0000230416.82349.90
|View full text |Cite
|
Sign up to set email alerts
|

SLCO1B1 polymorphism markedly affects the pharmacokinetics of simvastatin acid

Abstract: SLCO1B1 polymorphism markedly affects the pharmacokinetics of active simvastatin acid, but has no significant effect on parent simvastatin. Raised plasma concentrations of simvastatin acid in patients carrying the SLCO1B1 c.521C variant allele may enhance the risk of systemic adverse effects during simvastatin treatment. In addition, reduced uptake of simvastatin acid by OATP1B1 into the liver in patients with the c.521C allele could reduce its cholesterol-lowering efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
373
5
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(402 citation statements)
references
References 39 publications
19
373
5
5
Order By: Relevance
“…This contrasts with three small studies of pravastatin showing larger effects of rs4149056 on the lipid lowering response [3][4][5]. Simvastatin is given as a lactone prodrug but only the acid form of the drug is transported by OATP1B1 [6]. Pravastatin is given in the acid form so rs4149056 may have a larger effect with pravastatin than with simvastatin.…”
Section: British Journal Of Clinical Pharmacologymentioning
confidence: 43%
“…This contrasts with three small studies of pravastatin showing larger effects of rs4149056 on the lipid lowering response [3][4][5]. Simvastatin is given as a lactone prodrug but only the acid form of the drug is transported by OATP1B1 [6]. Pravastatin is given in the acid form so rs4149056 may have a larger effect with pravastatin than with simvastatin.…”
Section: British Journal Of Clinical Pharmacologymentioning
confidence: 43%
“…For example, it has been reported that carriers of the single nucleotide polymorphism (SNP), c.521T4C (p.Val174Ala), OATP1B1*5 or *15, show increased plasma concentrations of pravastatin, 6-8 repaglinide 9 and simvastatin. 10 Severe toxicity after irinotecanbased chemotherapy for lung cancer has also been reported in a patient with a homozygote for the SLCO1B1*15 allele, which carries the SNP c.521T4C (p.Val174Ala). 11 The SLCO1B1 gene possesses many SNPs and mutations.…”
Section: Introductionmentioning
confidence: 96%
“…The oxidative metabolism of simvastatin acid is catalyzed primarily by CYP3A4 [10] . Additionally, simvastatin and its hydrolysate simvastatin acid are substrates of organic anion transporting polypeptide 1B1 (OATP1B1/Oatp2) [11][12][13][14] , an influx transporter expressed on the sinusoidal membrane of hepatocytes. Recent studies have shown that OATP1B1 plays a clinically important role in the hepatic elimination of several drugs including statins, via mediating the hepatic uptake [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, simvastatin and its hydrolysate simvastatin acid are substrates of organic anion transporting polypeptide 1B1 (OATP1B1/Oatp2) [11][12][13][14] , an influx transporter expressed on the sinusoidal membrane of hepatocytes. Recent studies have shown that OATP1B1 plays a clinically important role in the hepatic elimination of several drugs including statins, via mediating the hepatic uptake [11][12][13][14][15] . Both clinical trials and animal experiments have demonstrated that DM may alter the pharmacokinetic behaviors of some drugs via regulating the expressions and activities of cytochrome P450s (CYP450s) and drug transporters in the liver [16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%